Bilateral Tension Pneumothorax Related to Acupuncture. Issue 2 (June 2013) - Tagami, Rumi; Moriya, Takashi; Kinoshita, Kosaku; Tanjoh, Katsuhisa
We report on a patient with a rare case of bilateral tension pneumothorax that occurred after acupuncture. A 69-year-old large-bodied man, who otherwise had no risk factors for spontaneous pneumothorax, presented with chest pressure, cold sweats and shortness of breath. Immediately after bilateral pneumothorax had been identified on a chest radiograph in the emergency room, his blood pressure and percutaneous oxygen saturation suddenly decreased to 78 mm Hg and 86%, respectively. We confirmed deterioration in his cardiopulmonary status and diagnosed bilateral tension pneumothorax. We punctured his chest bilaterally and inserted chest tubes for drainage. His vital signs promptly recovered. After the bilateral puncture and drainage, we learnt that he had been treated with acupuncture on his upper back. We finally diagnosed a bilateral tension pneumothorax based on the symptoms that appeared 8 h after the acupuncture. Because the patient had no risk factors for spontaneous pneumothorax, no alternative diagnosis was proposed. We recommend that patients receiving acupuncture around the chest wall must be adequately informed of the possibility of complications and expected symptoms, as a definitive diagnosis can be difficult without complete information.